2007
DOI: 10.2500/ajr.2007.21.3103
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Nasal Mucus in Chronic Rhinosinusitis

Abstract: The field of proteomics has great potential in leading to a better understanding of the mechanism of the disease process in CRS. Differences in the expression of proteins related to regulation of immune cells and mediators merit additional investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
2
51
0
1
Order By: Relevance
“…Proteomic analysis showed that MUC5B was significantly overexpressed in CRS samples, whereas MUC5AC did not reach statistical significance. In line with our results, MUC5B, but not MUC5AC, has been identified by proteomic analyses of nasal mucus from CRS patients with nasal polyps (29).…”
Section: Mucins In Sinonasal Secretionssupporting
confidence: 91%
See 2 more Smart Citations
“…Proteomic analysis showed that MUC5B was significantly overexpressed in CRS samples, whereas MUC5AC did not reach statistical significance. In line with our results, MUC5B, but not MUC5AC, has been identified by proteomic analyses of nasal mucus from CRS patients with nasal polyps (29).…”
Section: Mucins In Sinonasal Secretionssupporting
confidence: 91%
“…Each has been identified in CRS samples. S100A9 is overexpressed in nasal secretory cells from CRS patients with nasal polyps (28), as well as nasal mucus (29) and nasal lavage fluid from CRS patients (19). S100A8 is overexpressed in sinonasal mucosa tissue from patients with CRS with nasal polyps (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein was also found to be upregulated in nasal mucus in a study of patients with chronic sinusitis. 12 Cystatin-S was upregulated in the symptomatic group at 20 min and in the asymptomatic group at 5 h. By contrast, in another study, lower levels of this protein were found in nasal fluids from persons suffering from seasonal allergic rhinitis compared to controls. 11 The levels of cystatin-SN in the asymptomatic group were lower than in the other two groups.…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, there has been an interest in identifying human nasal mucus and fluid-phase proteins using proteomics, particularly in relation with chronic rhinosinusitis and allergic rhinitis [43,44,45,46,47,48]. These studies focus on the protein profiling of diseases with the aim of determining biomarkers in nasal secretions.…”
Section: Discussionmentioning
confidence: 99%